Productivity and economic benefits of coconut based vegetable cropping systems under central dry zone of Karnataka - H.P. Maheswarappa, K.S. Naveen Kumar; Basavaraju, T.B. (Journal of Plantation Crops, 2017)
Coconut based cropping systems with vegetables i.e., okra-fallow (2012-13) and tomato-fallow (2013-14), green manure-cucumber, baby corn-gherkin and coconut monocropping as control with four integrated nutrient management (INM) practices viz., inorganic fertilizer alone (100%), 5 ton farm yard mannure (FYM)+75% NPK+25% N by vermicompost (VC), 5 ton FYM+50% NPK+25% N by vermicompost+25% N by composted coir pith (CCP)+ Indian Institute of Horticulture Research (IIHR) micronutrient spray and 5 ton FYM+50% N by vermicompost+50% N by CCP+vermiwash spray+Azatobacter were evaluated at HRS, Arsikere, Karnataka during the year 2012 to 2014 by adopting factorial RBD with five replications. All the vegetable crops gave the highest yield under integration of organic and inorganic manure treatments, viz., 5 tonne FYM+74% NPK +25% N by VC and 5 ton FYM+50% NPK+25% N by vermicompost+25% N by CCP+IIHR micronutrient spray, whereas the lowest vegetables yield was noticed with 5 ton FYM+50% N by vermicompost+50% N by CCP + vermiwash spray + Azatobacter. Cropping sequence, baby corn-gherkin resulted in the highest coconut equivalent yield of intercrops and cropping system (33,548 nuts ha-1 and 44,414 nuts ha-1, respectively). Pooled economic analysis indicated that, okra-fallow and tomato-fallow sequence resulted in significantly higher net income (` 4,03,551 ha-1) compared to other sequences and it was on par with baby corn-gherkin sequence (` 3,60,365 ha-1).